Toward an Integrated, Systemic, and Sustainable Model of Transformational Family Engagement: The Case of the Kentucky Statewide Family Engagement Center - Danielle M. Perry; Joanna Geller (Social Sciences, 2021)
Transformational family engagement fundamentally changes relationships between families and schools and interrupts deeply held beliefs about low-income, Black, Latinx, Indigenous, or immigrant families, each of which are rooted in systems of racism, classism, sexism, xenophobia, and their intersections. In this paper, we use a community-based collective impact theoretical framework to better understand how the KY Collaborative is aligned with transformational family engagement strategies and promotes and implements systemic, statewide evidenced-based family engagement policies and practices. We present data from interviews with KY Collaborative partners, observations of KY Collaborative events and activities, and survey data. Key findings suggest the KY Collaborative leverages each regional partner’s strengths to break through historical barriers that fail to acknowledge the critical role families play both within and outside of schools. Their collective programs and services demonstrate a commitment to strengthening families, building capacity amongst schools and educators, and supporting communities to achieve educational equity. Our findings present implications for other statewide family engagement centers and community-based collaborations for transformational family engagement by highlighting the ways in which the KY Collaborative develops bottom-up leadership, builds dual capacity, shifts power, attends to policy change, and diffuses shared messages, visions, and practices statewide.